Roa and Eva: A Comparative Empirical Study - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
This research examines the influence of Economic Value Added (EVA) and Returns On Assets (ROA) to the stock returns. EVA is a new method to asses company's performance. EVA is expected to imply an important information for the investor. The fact is that for ILQ 45 companies, the ROA measure has a better relationship with the share's returns compared to EVA. EVA was also found statistically trot significant in explaining the rate of stock returns. The explanation of this finding is that of EVA has not been used and reported in financial statement, so that the investors do not use it yet in decision making.